2020
DOI: 10.1002/ls.1489
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the high‐speed wheel/rail adhesion under the starved interfacial contaminations with surface roughness

Abstract: This paper presents a new numerical model of wheel/rail in rolling contact to study the adhesion mechanism under the starved interfacial contaminations at high speed considering surface roughness. A thermal starved mixed elastohydrodynamic lubrication (EHL) theory is hired in the model. The empirical equations for analysing the contact force of rough surfaces that are based on amount of accurate finite element analysis (FEA) of an elastic‐plastic single‐asperity contact over a rigid flat are proposed. Multilev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…(4) Oil for lubrication increases, but oil for cooling decreases as the modulus increases. (5) As the number of teeth increases, the oil volume for lubrication increases, but the oil volume for cooling decreases. (6) The rangeability of the oil volume for lubrication along the mesh line (i.e., the slope of the curve of the oil volume for lubrication) increases as the transmission ratio increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Oil for lubrication increases, but oil for cooling decreases as the modulus increases. (5) As the number of teeth increases, the oil volume for lubrication increases, but the oil volume for cooling decreases. (6) The rangeability of the oil volume for lubrication along the mesh line (i.e., the slope of the curve of the oil volume for lubrication) increases as the transmission ratio increases.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the published literature shows that the field of gear lubrication has two major research focuses. The first focuses on the state of the lubricating oil film on the meshing tooth surfaces, including the model analysis of EHL, in order to establish the nonlinear relationships among oil film thickness, pressure and density [4]; numerical methods for solving the EHL [5]; and measurement of and experimentation on the contact area [6]. The second group focuses on the use of commercial computational fluid dynamics (CFD) software to simulate the flow state of lubricating oil during the gear meshing process and visualise the flow field of lubricating oil [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also analyzed the influence of the different physical properties of water and oil on the adhesion characteristics. They found that the adhesion coefficient decreased faster than that of water in the presence of oil pollution on wheel-rail surface, and explained the causes from the numerical point of view [84][85][86]. Chen H et al developed a three-dimensional calculation model using the mixed lubrication theory to numerically analyze the adhesion characteristics in a water medium.…”
Section: Adhesion Theory and Mechanism Of High-speed Wheel-rail In Ro...mentioning
confidence: 99%
“…The obtained result has theoretical significance, but the prediction of actual wheel-rail adhesion needs careful consideration. To this end, Wu B et al extended their two-dimensional model to a three-dimensional model [88]. The geometric dimensions and actual normal load at the wheel-rail contact point of a CRH2 high-speed train were considered in modeling and analyzing.…”
Section: Adhesion Theory and Mechanism Of High-speed Wheel-rail In Ro...mentioning
confidence: 99%
See 1 more Smart Citation